Journal of Translational Medicine - Marincola, Francesco M.
Journal of Translational Medicine is an open access journal publishing articles focusing on information derived from human experimentation so as to optimise the communication between basic and clinical science. The journal covers all areas of translational medicine but also has several specialized sections: Cancer microenvironment - Edited by Davide Bedognetti Cardiovascular, metabolic and lipoprotein translation- Edited by Nehal N. Mehta Cell, tissue and gene therapy - Edited by David Stroncek Clinical translation - Edited by Lana Kandalaft Combination strategies - Edited by Paolo A. Ascierto Computational modelling and Epidemiology- Edited by Michael Liebman and Sabrina Molinaro Disease biomarkers - Edited by Xiangdong Wang Illnesses of Unknown Etiology - Edited by Monica Panelli Immunobiology and immunotherapy - Edited by Alessandra Cesano Immunovirology - Edited by Luigi Buonaguro Medical bioinformatics - Edited by Samir K. Brahmachari Neuroscience - Edited by Luis F. Alguacil Nutrition & metabolism - Edited by Laura Soldati Pain, critical care and anesthesia - Edited by Yasin S. Al Makadma Patient-targeted molecular therapies - Edited by Francesco Chiappelli Personalised medicine - Edited by Lotfi Chouchane Translational imaging - Edited by Ravinder Reddy Translational hematology- Edited by Seah H. Lim.